1993
DOI: 10.1095/biolreprod48.6.1334
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptides Synthesized and Released by Rat Ectopic Uterine Implants Differ from those of the Uterus in Culture1

Abstract: Unique endometriosis-specific secretory proteins would be of paramount importance as noninvasive markers for diagnosis and evaluation of therapeutic approaches for endometriosis. Furthermore, identification of endometriosis-specific secretory proteins may be an important step towards understanding the pathophysiology of endometriosis-associated pain and infertility. Therefore this study was designed to assess protein synthesis and secretion by ectopic uterine implants from steroid-treated and reproductively cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 17 publications
(16 reference statements)
1
21
0
1
Order By: Relevance
“…The rat ectopic and eutopic endometrium have the same differential secretory pattern of protein synthesis and are histologically similar to what has been observed in human endometriosis. Furthermore, rats with surgically induced endometriosis exhibit a decrease in their fecundity and NK cell activity that parallels the human disease (8)(9)(10)(11). Moreover, we have recently shown that, similar to the human disease, this animal model is characterized by a dysregulation of the TNF system systemically and at the peritoneal level (12).…”
Section: Introductionmentioning
confidence: 69%
“…The rat ectopic and eutopic endometrium have the same differential secretory pattern of protein synthesis and are histologically similar to what has been observed in human endometriosis. Furthermore, rats with surgically induced endometriosis exhibit a decrease in their fecundity and NK cell activity that parallels the human disease (8)(9)(10)(11). Moreover, we have recently shown that, similar to the human disease, this animal model is characterized by a dysregulation of the TNF system systemically and at the peritoneal level (12).…”
Section: Introductionmentioning
confidence: 69%
“…For experiments 2 and 3, endometriosis was surgically induced in rats (Endo) as previously described by Vernon and Wilson [13] and routinely performed in our laboratory [19,21,33,34,37,38]. A unilateral ovariohysterectomy was performed, and sections of the removed uterus were autotransplanted into the arterial cascade of the small intestine.…”
Section: Induction Of Endometriosismentioning
confidence: 99%
“…TIMP1 represents at least 10% to 15% of proteins secreted into the peritoneal cavity by both rat implants and human endometriotic lesions [33,35]. Because products from endometriotic lesions in the peritoneal fluid (PF) bathe the ovary and enter the uterus through the oviducts, endometriotic TIMP1 may influence the entire reproductive system, including ovulation, oocyte quality, embryo development, and early spontaneous pregnancy loss [17].…”
Section: Introductionmentioning
confidence: 99%
“…Few endometriosis-specific proteins, secreted in vitro by endometriotic tissue in a rat model, have been identified using the proteomics approach (25,26). Protein profiles of eutopic endometrium (EUE) of women with and without endometriosis have also been compared (27,28).…”
mentioning
confidence: 99%